Batasan Penggunaan Hak Ingkar Notaris Terhadap Kewajiban Menjaga Kerahasiaan Akta - Komang Sulistyawati; I Wayan Novy Purwanto (Fakultas Hukum, Universitas Warmadewa, 2025)
The notary holds a crucial role as a public official authorized by the state to ensure legal certainty and protection through the creation of authentic deeds. One of the notary’s principal responsibilities is to maintain the confidentiality of deeds, a duty that is legally protected through the right of refusal (recht van verschoning). However, in notarial practice, conflicts often arise between the obligation to uphold professional confidentiality and the demands of law enforcement when a notary is requested to testify in court. This situation reflects a gap between legal theory and the practical implementation of the right of refusal in Indonesia. This study aims to examine the legal regulations governing the notary’s right of refusal and analyze the limits of its application in relation to the obligation to maintain deed confidentiality. The research employs a normative juridical method with a statutory approach. It also provides a descriptive analysis of primary and secondary legal materials related to the notary’s right of refusal, including the Notary Office Law, the Criminal Code, the Criminal Procedure Code, the Civil Code, and the Notary Code of Ethics. The findings indicate that the right of refusal has a strong legal foundation as a form of protection for professional secrecy; however, its application is limited. This right may be set aside when mandated by law, in cases involving higher legal interests, or with the approval of the Honorary Council of Notaries (Majelis Kehormatan Notaris, MKN).